IN VITRO EVALUATION OF THE CYTOTOXICITY AND BIOCOMPATIBILITY OF VIDANGADI KSHARA ON LYMPHOMA CANCER CELLS - Pallavi Athavale; Veena B. Kupatib
The global leading cause of mortality is cancer, with approximately 10 million cancer-related deaths documented in 2020. Vidangadi kshara (VK), a formulation containing Vidanga, Chitraka, Shunthi, Ghrita, Saindhava and Vacha, is traditionally prescribed for Gulma (lump) and Pleeha vyadhi (spleenomegaly). This research aims to evaluate the potential cytotoxic effects and biocompatibility of Vidangadi kshara against lymphoma cells, while assessing its impact on normal cells.The Vidangadi kshara preparation followed classical methodologies and underwent quality analysis according to standard guidelines before being tested for anticancer properties using the tetrazolium-based MTT assay. In mouse fibroblast L929 cells, VK demonstrated cell viability results comparable to cisplatin. When administered at a dose of 1mg, VK exhibited cytotoxic activity against Daudi and Raji Burkitt lymphoma cells. The percentage of cell viability observed with VK treatment was similar to that achieved with cisplatin treatment.